Cancer immunotherapy and its renal effects. Issue 3 (October 2019) - Mamlouk, Omar; Abudayyeh, Ala
With the advent of the era of immunotherapy, there has been marked increased survival in several cancers such as advanced melanoma, renal cell carcinoma, non-small cell lung cancer, urothelial carcinoma, and head and neck cancers. Harnessing the immune system against tumor by releasing the breaks off the regulators of the immune system, such as cytotoxic T-lymphocyte–associated antigen 4, programmed cell death protein 1, and its ligand, has resulted in also unregulated organ-specific toxicity. In this review, we will discuss the renal toxicities associated with a checkpoint inhibitor from the typical acute tubulointerstitial nephritis to glomerulonephritis and their proposed mechanisms. In addition, we discuss the available data associated with transplant rejection and the use of checkpoint inhibitor.